Performance of Backpropagation Algorithm in Recognizing Patterns on Finger Print Machines at Jaya Krama Beringin Private Vocational School Using Artificial Neural Network - Sutini Sutini; R. Fanry Siahaan (Journal of Intelligent Decision Support System (IDSS), 2020)
This research is about Artificial Neural Networks in Identifying Patterns on Finger Print Machines at the Jaya Kerama Beringin Private Vocational School. The method used is Backpropagation, Backpropagation is applied to determine the finger print machine user with criteria, whether he arrives on time, is he late, and whether go home too early or come home on time. The system was built using Visual Studio 2010 programming language with Microsoft Access 2007 database. The result of this research is a finger print attendance application that identifies the attendance machine user which can help Jaya Kerama Vocational High School in controlling the discipline of teachers and employees.